2021
DOI: 10.1111/josh.13005
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Differences in Protective School Assets by Sexuality, Gender, Race/Ethnicity, and Socioeconomic Status

Abstract: BackgroundSchool assets—such as connectedness, caring relationships with adults, high behavioral expectations from adults, and meaningful participation—are associated with positive outcomes for adolescents. However, little is known about how school assets differ among adolescents with intersecting marginalized identities.MethodsWe used the 2013‐2014 California Healthy Kids Survey (N = 320,462 students) to examine differences in school assets with respect to sexuality, gender, race/ethnicity, and socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Bisexual women/girls have the highest rate of binge drinking 45. A recent study reported youth with multiple marginalised identities, such as sexual identity, racial identity, cultural identity, gender identity and socioeconomic status (SES), experience stress differently than their peers, leading to injury inequity among diverse youth 46…”
Section: Methodsmentioning
confidence: 99%
“…Bisexual women/girls have the highest rate of binge drinking 45. A recent study reported youth with multiple marginalised identities, such as sexual identity, racial identity, cultural identity, gender identity and socioeconomic status (SES), experience stress differently than their peers, leading to injury inequity among diverse youth 46…”
Section: Methodsmentioning
confidence: 99%
“…School connectedness is particularly crucial for youth from marginalized groups. Sexual minority, gender minority, and racial/ethnic minority youth and those from low-socioeconomic status report lower school-related protective factors (including school connectedness), with even higher disparities among youth belonging to multiple marginalized groups (Coulter et al, 2021). The pandemic has negatively affected the mental health of LGBTQIA+ youth due to a lack of opportunities to socialize and build supportive, identity-affirming relationships that might bolster feelings of belongingness at school (Fish et al, 2020).…”
Section: Why Does School Connectedness Matter?mentioning
confidence: 99%
“…Unfortunately, sexual and gender minority youths are more likely than their heterosexual peers to lack supportive adults at school, have lower school connectedness, and be exposed to bullying [5,6,25,26,[31][32][33][34][35][36][37][38][39]]. An intervention that trains school staff to better understand and support sexual and gender minority youths and engage in positive bystander behaviors that protect them from bullying exposure may reduce health disparities among them.…”
Section: Introductionmentioning
confidence: 99%